Selective Histone Deacetylase 6 Inhibitor 23BB Alleviated Rhabdomyolysis-Induced Acute Kidney Injury by Regulating Endoplasmic Reticulum Stress and Apoptosis - Yuying Feng; Rongshuang Huang; Fan Guo; Yan Liang; Jin Xiang; Song Lei; Min Shi; Lingzhi Li; Jing Liu; Yanhuan Feng; Liang Ma; Ping Fu (Frontiers Media S.A., 2018)
Histone deacetylase 6 (HDAC6) contributed to the pathogenesis of rhabdomyolysis-induced acute kidney injury (AKI) and selective inhibition of HDAC6 activity may be a promising strategy for the treatment of AKI. Compound 23BB as a highly selective HDAC6 inhibitor was designed, synthesized by our lab and exhibited therapeutic potential in various cancer models with good safety. However, it remained unknown whether 23BB as a drug candidate could offer renal protective effect against rhabdomyolysis-induced AKI. In the present study, we investigated the effect of 23BB in a murine model of glycerol (GL) injection-induced rhabdomyolysis. Following GL injection, the mice developed severe AKI as indicated by acute renal dysfunction and histologic changes, accompanied by increased HDAC6 expression in the cytoplasm of tubular epithelial cells. Pharmacological inhibition of HDAC6 by 23BB pretreatment significantly reduced serum creatinine and serum blood urea nitrogen (BUN) levels as well as attenuated renal tubular damage in GL-injured kidneys. HDAC6 inhibition also resulted in reduced TdT-mediated dUTP nick-end labeling (TUNEL)-positive tubular cells, suppressed BAX, BAK, cleaved caspase-3 levels, and preserved Bcl-2 expression, indicating that 23BB exerted potent renoprotective effects by the regulation of tubular cell apoptosis. Moreover, GL-induced kidney injury triggered multiple signal mediators of endoplasmic reticulum (ER) stress including GRP78, CHOP, IRE1α, p-eIF2α, ATF4, XBP1, p-JNK, and caspase-12. Oral administration of 23BB improved above-mentioned responses in injured kidney tissues and suggested that 23BB modulated tubular cell apoptosis via the inactivation of ER stress. Overall, these data highlighted that renal protection of novel HDAC6 inhibitor 23BB is substantiated by the reduction of ER stress-mediated apoptosis in tubular epithelial cells of rhabdomyolysis-induced AKI.